PRODUKSI CETAKAN HANDLE PINTU BERBANTU MESIN CNC MCV-720 - Fauzan, Azkal Rafi; Syarifudin, Syarifudin; Sapriyanto, Eko; Safinatunnaja, Indy (Nozzle : Journal Mechanical Engineering, 2024)
A door handle is a door component whose function is to make it easier to control the door, increase the security of the room, and add to the aesthetics of the room. Permanent molds are a solution to the shortcomings of sand molds to produce high quality products and are economical in terms of costs. This research aims to produce door handle molds using ST 41 steel material. Research on the production of door handle molds goes through stages starting from making the design, followed by creating a program, operations such as turning on the MCV-720 CNC machine, then continuing with the Zero Return process, installing the workpiece, setting X, Y, and Z to the process of running the program via the NC application. Meanwhile, the post-programming stages are the Facing process (flattening the side of the workpiece), Contouring (making a track on the workpiece), Pocketing (refining the track on the workpiece) and Drilling (making holes in the workpiece) using the MCV-720 CNC machine produces smooth and precise products with dimensions of 120 mm long and 70 mm wide.